Library and information center management - Stueart, Robert D.; Moran, Barbara B.; Morner, Claudia J. (2013)
"This updated edition of the renowned library management textbook provides a comprehensive overview of the techniques needed to effectively manage a contemporary library or information center"--
First through third editions, published 1977-1987, have title Library management; Fourth through seventh editions, authored by Robert D. Stueart and Barbara B. Moran and published 1993-2007, have title Library and information center management.
Includes bibliographical references and index.
Keywords: Library administration; Library administration -- United States; Information services; Information services -- United States